TRANSDUCERS 2009 - 2009 International Solid-State Sensors, Actuators and Microsystems Conference 2009
DOI: 10.1109/sensor.2009.5285421
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the quality factor of microcantilever using hydrodynamic coupling of micro structures

Abstract: This study demonstrates the concept of controlling the quality factor of a micro-cantilever using hydrodynamic coupling of active mechanical structures. The active micro structures (auxiliary-cantilevers) adjacent to the micro-cantilever (operating-cantilever) are exploited to generate hydrodynamic force to change the air damping of the operating-cantilever. Thus, the quality factor of operating-cantilever can be increased or decreased by changing the phase of the excitation force on the auxiliary-cantilevers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The use of micro-cantilevers as transducers in biochemical sensing systems has increased in recent years. Many research efforts in this field have been reported (Ramos et al, 2006;Mahmoodi and Jalili, 2007;Mahmoodi et al, 2008;Lee et al, 2009). Several works have modeled the vibrational dynamics of cantilever-type devices operated in air (Yum et al, 2004), liquid (Zhang and Turner, 2007;Chon et al, 2000), and vacuum (Burns et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The use of micro-cantilevers as transducers in biochemical sensing systems has increased in recent years. Many research efforts in this field have been reported (Ramos et al, 2006;Mahmoodi and Jalili, 2007;Mahmoodi et al, 2008;Lee et al, 2009). Several works have modeled the vibrational dynamics of cantilever-type devices operated in air (Yum et al, 2004), liquid (Zhang and Turner, 2007;Chon et al, 2000), and vacuum (Burns et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the advantages of enhancing the quality factor, tuning the quality factor to a prespecified value would also increase the dynamic performance of resonant cantilever sensors (Lee et al, 2009). For determining liquid densities by PEMC, for example, the resonant frequency of the cantilever would change principally because of the liquid density variations (displaced mass effect).…”
Section: Introductionmentioning
confidence: 99%